Permainan Tradisional Indonesia Untuk Meningkatkan Wawasan Karir Siswa - Juliyanti, Novi; Prabowo, Arga Satrio; Conia, Putri Dian Dia (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Study This based on problems that occur in teenagers , generally problem That about lack of understanding career . One of way that can be used For solve problem This is give service information in Bim bingan and counseling , with use creative media . Research and development This done aim For developing guidance and counseling media shaped game traditional cranky . Research methods used​ in study This is research and development (R&D) with draft Thiagarajan 4D model development . There are 4 stages carried out namely Define , Design , Development , Disseminate .​ Test subjects​ study This are 6 students class XI of SMAN 11 Pandeglang which has outlook career low . Data collection techniques were carried out use instrument questionnaire . On testing material and language product game traditional cranky get a score of 90, 90% or 'very good ', then in the game media test traditional cranky get a score of 80% or 'very decent '. From the test results limited student give value